PENGARUH AKSESIBILITAS FISIK DAN EKONOMI TERHADAP PERSEPSI PETANI DALAM PEMANFAATAN COMBINE HARVESTER (STUDI KASUS DI KECAMATAN TULANGAN, KABUPATEN SIDOARJO) - Samputri, Ghea Lintang; Hendrarini, Hamidah; Antriyandarti, Ernoiz (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2025)
The combine harvester has been proven to improve rice harvest productivity. however, not all farmers can easily access this machinery due to limited availability and infrastructure. This study aims to evaluate the influence of availability-both physical and economis-on rice farmers’ perceptions regarding the utilization of Combine Harvester. A quantitative approach was employed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) analysis method. Primary data were collected through direct interviews, while secondary data were obtained from official archives of the Tulangan Agricultural Extension Office (BPP Tulangan). The analysis results indicate that economic access has a significanteffect on perceived usefulness (t= 2,794 > 1,96) and perceived ease of use (t= 3,031 > 1,96). Furthermore, physical access also shows a significant influence on perceived usefulness (t= 2,544 > 1,96) and perceived ease of use (t= 3,086 > 1,96). In addition, perceived ease of use significantly affects perceived usefulness with a t-value of 2,590 > 1,96)